MAḤABBAH AND FANĀ’: NARRATIVE SEMIOTICS OF SUFIS VALUES IN THE SHORT STORY “ARINĪ ALLĀH” BY TAUFĪQ AL-ḤAKĪM - Uswatun Khasanah; Moh Sony Fauzi (CMES (Center of Middle Eastern Studies), 2025)
This study aims to analyze the values of Sufism, particularly the concepts of maḥabbah (divine love) and fanā’ (annihilation of the self), as reflected in the short story “Arinī Allāh” by Taufīq al-Ḥakīm, using the narrative semiotic approach based on A. J. Greimas’s theory. The research seeks to uncover the representation of Sufi values within the narrative structure and their influence on the development of the main character. A qualitative descriptive method was employed, with data collected through a close reading of the story and note-taking based on the theoretical framework. The data were analyzed using the Miles and Huberman model, which involves data collection, data reduction, data display, and conclusion drawing. The findings indicate that the story contains clear elements of the protagonist’s spiritual journey in search of the essence of God, which cannot be perceived physically but may be experienced through divine love. These results contribute to the enrichment of literary and Sufi studies by demonstrating how Sufi values are embedded within modern literary works through narrative semiotic analysis.